2011
DOI: 10.1242/jcs.083659
|View full text |Cite
|
Sign up to set email alerts
|

BMP2, but not BMP4, is crucial for chondrocyte proliferation and maturation during endochondral bone development

Abstract: SummaryThe BMP signaling pathway has a crucial role in chondrocyte proliferation and maturation during endochondral bone development. To investigate the specific function of the Bmp2 and Bmp4 genes in growth plate chondrocytes during cartilage development, we generated chondrocyte-specific Bmp2 and Bmp4 conditional knockout (cKO) mice and Bmp2,Bmp4 double knockout (dKO) mice. We found that deletion of Bmp2 and Bmp4 genes or the Bmp2 gene alone results in a severe chondrodysplasia phenotype, whereas deletion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
179
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(199 citation statements)
references
References 59 publications
14
179
0
Order By: Relevance
“…Therefore, we examined the humeral expression pattern of Bmp4 using ISH. In accordance with earlier reports of Bmp4 expression in the growth plate (Isshiki et al, 2011;Shu et al, 2011), we found that Bmp4 is expressed weakly in the prehypertrophic zone and more strongly in the hypertrophic region of the E13.5 humerus (Fig. 3E).…”
Section: Shox2 Regulates Chondrogenesis 6073supporting
confidence: 93%
“…Therefore, we examined the humeral expression pattern of Bmp4 using ISH. In accordance with earlier reports of Bmp4 expression in the growth plate (Isshiki et al, 2011;Shu et al, 2011), we found that Bmp4 is expressed weakly in the prehypertrophic zone and more strongly in the hypertrophic region of the E13.5 humerus (Fig. 3E).…”
Section: Shox2 Regulates Chondrogenesis 6073supporting
confidence: 93%
“…BMP-2's contribution to matrix formation, there are a few reports studying its function in chondrocyte proliferation [34,38]. However, qPCR data from the xenogenic co-culture model indicated that expression of BMP-2 appeared to be increased predominantly in hPCs but not in MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Among these genes, BMP-2 and FGF-1 stood out, as their functions in chondrocyte proliferation and matrix formation had been previously demonstrated [32][33][34]. For a long time, BMP-2 has been used as a strong stimulator for osteogenic differentiation of stem cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…Selected polymorphisms in the BMP2 gene are associated with increased fracture risk and osteoporosis (Styrkarsdottir et al, 2003). Deletion of other BMP family members Bmp7 and Bmp4 suggests that they play minor roles in bone and cartilage development in the embryo or postnatally, whereas Bmp2 is critical for chondrocyte function and endochondral bone development Shu et al, 2011;Tsuji et al, 2008). Removal of Bmp2 in mouse mesenchymal precursor cells in 10 d.p.c.…”
Section: Introductionmentioning
confidence: 99%